IL1- and TGFβ-Nox4 signaling, oxidative stress and DNA damage response are shared features of replicative, oncogene-induced, and drug-induced paracrine 'bystander senescence' - Hubackova, Sona; Krejcikova, Katerina; Bartek, Jiri; Hodny, Zdenek (Aging, 2012)
Many cancers arise at sites of infection and inflammation. Cellular senescence, a permanent state of cell cycle arrest that provides a barrier against tumorigenesis, is accompanied by elevated proinflammatory cytokines such as IL1, IL6, IL8 and TNFα. Here we demonstrate that media conditioned by cells undergoing any of the three main forms of senescence, i.e. replicative, oncogene- and drug-induced, contain high levels of IL1, IL6, and TGFb capable of inducing reactive oxygen species (ROS)-mediated DNA damage response (DDR). Persistent cytokine signaling and activated DDR evoke senescence in normal bystander cells, accompanied by activation of the JAK/STAT, TGFβ/SMAD and IL1/NFκB signaling pathways. Whereas inhibition of IL6/STAT signaling had no effect on DDR induction in bystander cells, inhibition of either TGFβ/SMAD or IL1/NFκB pathway resulted in decreased ROS production and reduced DDR in bystander cells. Simultaneous inhibition of both TGFβ/SMAD and IL1/NFκB pathways completely suppressed DDR indicating that IL1 and TGFβ cooperate to induce and/or maintain bystander senescence. Furthermore, the observed IL1- and TGFβ-induced expression of NAPDH oxidase Nox4 indicates a mechanistic link between the senescence-associated secretory phenotype (SASP) and DNA damage signaling as a feature shared by development of all major forms of paracrine bystander senescence.
Keywords: stárnutí buněk; Paracrine Communication; proteiny Smad; transfekce; oxidační stres; RNA interference; poškození DNA; Cell Line; Interleukin-1; bystander efekt; DNA Damage; Janus kinasy; Transforming Growth Factor beta; Cell Proliferation; NADPH Oxidase 4; NADPH-oxidasy; Transfection; Culture Media, Conditioned; Janus Kinases; signální transdukce; Interleukin-6; parakrinní signalizace; STAT Transcription Factors; interleukin-1; NADPH-oxidasa 4; etoposid; Cellular Senescence; Smad Proteins; kultivační média speciální; Signal Transduction; transformující růstový faktor beta; Genes, ras; geny ras; lidé; transkripční faktory STAT; interleukin-6; Humans; NF-kappa B; buněčné linie; proliferace buněk; Bystander Effect; Oxidative Stress; NADPH Oxidases; RNA Interference; Etoposide